Pembentukan Karakter Religius Peserta Didik Melalui Kegiatan Pembiasaan Tadarus Al-Qur'an di SMPN 3 Bojong - Tamimi, Tubagus Ahda; Sulistiana; Widodo Hami (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2022)
Habituation is an action that is carried out continuously as an effort to form an attitude in a person. In the process of habituation is identical to the way of repetition so as to form a habit. Efforts to form religious character in participants are by habituation of tadarus. This research was conducted at SMPN 3 Bojong which aims to determine the effect of tadarus habituation as an effort to build religious character and to find out the obstacles in the habituation process. The subjects in this study were students at SMPN 3 Bojong. This research is a field research with a qualitative approach using a descriptive method. Data collection techniques in this study using observation and interview techniques. After doing the research, it can be concluded that the formation of the religious character of students through the habituation activity of tadarus al-Qur'an at SMPN 3 Bojong went well where this habituation was carried out regularly and brought out the religious character of the students. However, there are several obstacles, namely the lack of facilities and infrastructure, lack of awareness of students, and the different backgrounds of students.